SUBJECTIVE WELL-BEING AND ENGAGEMENT IN COMMUNITY SPORTS ACTIVITIES - Ioannis PAPAIAKOVOU; Nelly-Eleni PAVLIDOU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2018)
Physical activity and sports participation have significant benefits for physical and mental well-being, an emerging literature examines the impact of sports participation on subjective well-being. Identifying the existing literature gap regarding sport attending’s relationship with subjective well-being, this study will examine whether sport attending also have significant and positive effects on individuals’ life satisfaction. This study seeks to establish a relationship between sports participation and subjective well-being by distinguishing active and non-active participation. Subjective well-being was measured through life satisfaction in a sample of 1,017 active and non-active participants in a local Marathon event. Individuals who actively participated in the Marathon event reported higher life satisfaction compared to non-active participants. Education and frequency of participation were found to be significant mediation factors of the sports participation - subjective well-being relationship, with more educated and more frequent participants reporting higher life satisfaction. Engagement in community sports activities upgrades subjective well-being, and the power of this relationship is affected by specific demographic variables.